2016
DOI: 10.18203/2320-6012.ijrms20164545
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of transfusion transmitted infections amongst multiple blood transfused patients of β-thalassemia major in a tertiary care hospital

Abstract: Background: The β-thalassemias are the most common autosomal recessive inherited hemoglobin disorder in the Indian subcontinent, with an uneven distribution among different endogenous populations. Present study was planned to estimate the prevalence of transfusion transmitted viral diseases in multiple transfused patients of β-thalassemia and factors affecting it.Methods: It was a Prospective observational study carried out at Thalassemia day care center of tertiary health care institute.Results: 211 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 1 publication
3
5
0
Order By: Relevance
“…Frequent blood transfusions increase the risk of TTI transmission. This was in concordance with the findings of Atwa and Abdel Wahed,[ 10 ] Mansour et al ,[ 21 ] Bhavsar et al [ 25 ] and Mittal et al [ 14 ] which found out the frequency of blood transfusion as an important determinant of TTIs. However, there are contrary evidence too, reported by Mahmoud et al [ 15 ] and Biswas et al [ 16 ] The variability of findings may be due to their small sample sizes compared to us.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Frequent blood transfusions increase the risk of TTI transmission. This was in concordance with the findings of Atwa and Abdel Wahed,[ 10 ] Mansour et al ,[ 21 ] Bhavsar et al [ 25 ] and Mittal et al [ 14 ] which found out the frequency of blood transfusion as an important determinant of TTIs. However, there are contrary evidence too, reported by Mahmoud et al [ 15 ] and Biswas et al [ 16 ] The variability of findings may be due to their small sample sizes compared to us.…”
Section: Discussionsupporting
confidence: 92%
“…Table 5 shows the burden of TTIs as reported by various studies and the current study. In our study, 34.5% of study participants were anti-HCV positive which was concurrent to findings of Mittal et al [ 14 ] (35.5%) and Mahmoud et al [ 15 ] (37.1%). There were studies which reported more[ 9 21 ] and vice versa[ 10 16 17 18 19 20 22 23 24 25 ] compared to our study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This finding is comparable to other studies. 4,6,7 In the study done by Mittal et al 14 , 66.6% of the patients who had received more than 400 blood transfusions were seropositive for Anti-HCV. There is a reduction in the development of anti-HCV post 2001, but it has not been eliminated.…”
Section: Discussionmentioning
confidence: 96%
“…Blood transfusion practices challenge the life of thalassemia patients and can cause new medical problems such as transfusion-transmitted infections like HCV, HBV, HIV, and syphilis infections. 7 , 8…”
Section: Introductionmentioning
confidence: 99%